Produtos naturais e derivados, complexação com o rutênio visando aumento da atividade citotóxica - Graminha, Angelica Ellen (Universidade Federal de São Carlos, 2015)
This work involves the synthesis and characterization of three new series of ruthenium complexes containing gallic acid and derivatives cinnamic acid and salicylic acid and derivatives, as these ligands exhibit interesting biological properties. All ligands are synthetic and natural products can be found in the daily diet. The interest in studying these three ligands series is due to the antioxidant power that some of these natural products present. Thus, complexes of formula [Ru(O-O)(dppb)(bipy)]PF6 and [Ru(O-O)(dppe)2]PF6 , where O-O = gallic acid and derivatives, cinnamic acid and salicylic acid and derivatives (bipy = 2,2'-bipyridine, dppb = 1,4-bis(diphenylphosphino)butane and dppe = 1,2- bis(diphenylphosphino)ethane). All the synthesized compounds were characterized by molar conductivity, elemental analysis, absorption spectra in the infrared, absorption spectroscopy in the UV-visible region, mass spectrometry, nuclear magnetic resonance 31P {1H}, cyclic voltammetry and differential pulse, and for some complexes, X-ray crystallography. The evaluation of the biological potential of ruthenium complexes with different series of ligands were evaluated: the partition coefficient, the antioxidant activity, morphological study, clonogenic assay in MDA-MB-231 and L929, cytotoxic activity in tumor cell lines MDA MB-231, MCF-7 and A549, and nontumor cell lines of mouse and hamster V79 and L929, respectively. Cell viability assays show promising results, indicating a greater cytotoxicity of the complexes in MDA-MB-231 line with respect to the other tumor cell line. Furthermore, the complexes of general formula [Ru(O-O)(dppe)2]PF6 exhibit the values lowest of IC50 in compared on the complexes of the general formula [Ru(O-O)(dppb)(bipy)]PF6 in all the cell line studied. Studies of the interaction of the complexes with bovine serum albumin (BSA), were performed, and compounds have moderate to strong interaction with the protein, and the complexes containing two dppe biphosphinas have smaller constant values in relation the complexes of the series [Ru(O-O)(dppb)(bipy)]PF6.
Natural products and derivatives, complexation with ruthenium targeting increased cytotoxicity activity
Keywords: Complexos de rutênio; Câncer; Produtos naturais; Atividade citotóxicas; Interação com BSA; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA